2022
DOI: 10.1080/16549716.2022.2047465
|View full text |Cite
|
Sign up to set email alerts
|

Spatial disparities in impoverishing effects of out-of-pocket health payments in Malawi

Abstract: Background Out-of-pocket health payments as a means of financing health services are a cause of concern among households in low and middle-income countries. They prevent households from accessing health care services, can disrupt households’ living standards by reducing consumption of other basic needs and push households into poverty. Previous studies have reported geographical variations in impoverishing effects of out-of-pocket health payments. Yet, we know relatively little about spatial effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In other words, it does not consider nor provide insight about households as potential financiers of COVID-19 care. Yet, studies have demonstrated the potential crowding out effects of household health payments on consumptions and on the risk for catastrophic health expenditures [8][9][10]. In Malawi, households contributions towards total health expenditure accounts for 12% and this contribution has been increasing consistently since 2012/13 [11].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it does not consider nor provide insight about households as potential financiers of COVID-19 care. Yet, studies have demonstrated the potential crowding out effects of household health payments on consumptions and on the risk for catastrophic health expenditures [8][9][10]. In Malawi, households contributions towards total health expenditure accounts for 12% and this contribution has been increasing consistently since 2012/13 [11].…”
Section: Introductionmentioning
confidence: 99%